2022
DOI: 10.1163/22134808-bja10071
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Tactile Flow on Visual Heading Perception

Abstract: The integration of information from different sensory modalities is crucial for successful navigation through an environment. Among others, self-motion induces distinct optic flow patterns on the retina, vestibular signals and tactile flow, which contribute to determine traveled distance (path integration) or movement direction (heading). While the processing of combined visual–vestibular information is subject to a growing body of literature, the processing of visuo-tactile signals in the context of self-moti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 30 publications
2
5
0
Order By: Relevance
“…Nevertheless, tactile stimuli were also clearly considered for heading perception. In sum, Bayes-nonoptimal multisensory integration as found in the present study was also reported in previous work ( 30 33 ) and can also be found in the case that tactile stimuli are not task relevant ( 15 ).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Nevertheless, tactile stimuli were also clearly considered for heading perception. In sum, Bayes-nonoptimal multisensory integration as found in the present study was also reported in previous work ( 30 33 ) and can also be found in the case that tactile stimuli are not task relevant ( 15 ).…”
Section: Discussionsupporting
confidence: 92%
“…The bias of perceived heading toward straight ahead is in line with results from the literature [Refs. 15 , 19 22 , but see also Ref. 8 , which found priors to the side (±90°)] and consistent with Bayesian accounts that have proposed a prior for straight ahead as the most common heading direction ( 21 , 23 ).…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…With a unique apparatus to provide airflow to the forehead in humans, the Bremmer group recently found that these airflow cues are integrated (sub-optimally) with visual cues of self-motion perception (Rosenblum, Grewe, et al, 2022;Rosenblum, Kreß, et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Despite evidence that airflow facilitates the feeling of vection (the sensation of movement of one’s body in space) even in humans (Seno et al, 2011; Murata et al, 2014; Kurosawa et al, 2017), the question whether, and to what extent, land animals use and integrate airflow information for self-motion perception has been little studied. With a unique apparatus to provide airflow to the forehead in humans, the Bremmer group recently found that these airflow cues are integrated (sub-optimally) with visual cues of self-motion perception (Rosenblum, Grewe, et al, 2022; Rosenblum, Kreß, et al, 2022). Whether more naturalistic airflow (e.g., that could be sensed across the whole body) would be integrated in line with Bayesian predictions of optimality remains an open question.…”
Section: Introductionmentioning
confidence: 99%